Lecture summaries - Smith, Christopher; Foster, Sally M; Richards, Eric (Proceedings of the Society of Antiquaries of Scotland, 1990)
Three lecture summaries: Cave dwelling in Mid-Argyll: recent and more distant past The spatial and social context of craft specialization in the Atlantic Province of Scotland from the time of the brochs to the arrival of the Norse Cromartie: The survival of a Highland estate and its people 1700-1914